STRATEGI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) PADA ANAK TUNAGRAHITA DI MI MA’ARIF SIDOMULYO AMBAL KEBUMEN - Witasari, Rinesti (BASICA, 2021)
Abstract: Starting from the results of observations at MI Ma'arif Sidomulyo Ambal Kebumen which is the only MI in Kebumen Regency that has organized an inclusive madrasah program, the researcher saw that there were a number of children with special needs (ABK) who received the same educational services as other normal children. aims to determine the planning and implementation of the PAI strategy in children with mental retardation, MI Ma'arif Sidomulyo Ambal Kebumen. The research method used is qualitative research, a descriptive type of field research with a case study approach. The results of the study, namely, the teacher planned a learning strategy with several stages and carried out a teacher-centered strategy individually, it can be seen that the learning methods are very varied, this is because the abilities possessed by mentally retarded children vary in achieving learning objectives.